THE NEW STAGE OF ECONOMIC DEVELOPMENT OF SUMQAYIT CITY (2019-2020 YEARS) - Ibrahimli Mehin Bayram (Theoretical Hypotheses and Empirical Results, 2025)
The new stage of economic development in Sumqayit city (2019-2020) focuses on the significant progress made in the industrial and economic sectors. During this period, Sumqayit continued its transformation into a modern industrial hub, with an emphasis on establishing new factories, improving infrastructure, and increasing local production. The city experienced a rise in the manufacturing of chemical, food, and light industry products, contributing significantly to the country’s economy. Key developments include the establishment of new industrial zones, particularly within the Sumqayit Chemical Industrial Park, which has become a major contributor to Azerbaijan’s non-oil sector. The city also witnessed an increase in foreign investment, job creation, and the implementation of large-scale infrastructure projects, resulting in a growing GDP and improved social-economic conditions. Overall, Sumqayit’s economic growth during 2019-2020 has been driven by modernizing existing industries, boosting manufacturing output, and fostering a competitive business environment, positioning it as one of Azerbaijan’s leading industrial cities.